TAMI-54. THE PRESENCE OF IMMUNE CELL INFILTRATES IN THE TISSUE MICROENVIRONMENT OF HIGH-GRADE GLIOMAS AND THEIR ASSOCIATION WITH OVERALL SURVIVAL. (9th November 2020) - Rishi, Anupam; Mohammadi, Homan; Martir, Daniela; Welsh, Eric; Robinson, Timothy; Oliver, Daniel; Eschrich, Steven; Torres-Roca, Javier; Yu, Hsiang-Hsuan; Grass, George; Ahmed, Kamran
Abstract: OBJECTIVE: Tumor-associated microglia and macrophages (TAMs) influence brain tumor biology and promote tumor-proliferating phenotype. Studies have shown these cell types predict outcomes in various tumor sites with limited evidence in high-grade gliomas (HGG). In this study, we assessed the presence of immune cell infiltrate (ICI) and overall survival (OS) in HGGs. METHODS: A total of 97 consecutively treated patients with primary HGG with complete gene expression profiling were identified from our IRB-approved institutional tissue biorepository. Patients underwent primary surgical resection between 02/2004 and 03/2011. Gene expression levels were assessed by Affymetrix Hu-RSTA assays (Affymetrix; Santa Clara, CA). CIBERSORT estimated the presence of ICI via gene expression deconvolution. Tumor characteristics and the presence of 22 individual ICI subtypes were assessed with respect to OS. Time-to-event analyses were performed with Kaplan-Meier estimates and compared via log-rank test. Associations between the ICI and outcomes were explored using Cox-regression. P < 0.05 (two-tailed) was considered statistically significant. RESULTS: Median follow-up from primary surgical resection was 12.8 months (range: 0.1-162.8), and median age was 58 years (20-85). Most patients were male (n=63; 65%) and had grade 4 tumors (n=71; 73%). OS differed by grade with 24-month actuarial OS rates of 81% and 34% ( P < 0.0001) for grade 3 and 4 gliomas, respectively. The presence of M0 (HR 2.2; 95% CI 1.4-3.6; P =0.001), M1 (HR 1.8; 95%CI 1.1-2.9; P =0.01), and M2 macrophages (HR 1.9; 95%CI 1.2-3.2; P =0.007) predicted OS. No other ICI subtypes were predictive of OS. The presence of M0- and M2-polarized macrophages were more common in grade 4 compared to grade 3 gliomas 46% vs. 11% ( P =0.002) and 69% vs. 31% ( P =0.0007), respectively. CONCLUSION: The increased presence of non-polarized or M2 TAMs within the glioma microenvironment was significantly associated with OS in HGG. Their presence may serve as unique stratification and a potential therapeutic target.